The impact of the nurses', doctors' and clinical officer strikes on mortality in four health facilities in Kenya - Grace Kiringa Kaguthi; Videlis Nduba; Mary Beth Adam (BMC, 2020)
Abstract Background Health worker strikes are a significant threat to universal access to care globally and especially in sub Saharan Africa. Kenya's health sector has seen an increase in such industrial action. Globally there is limited data that has examined mortality related to such strikes in countries where emergency services were preserved. We sought to assess the mortality impact of an 100 day physician strike which was followed by 151 day nurses' strike and 20 day clinical officer strike in Kenya. Methods Monthly mortality data was abstracted from four public hospitals, Kenyatta National Referral Hospital, AIC Kijabe Hospital, Mbagathi Hospital and Siaya Hospital between December 2016 and March 2018. Differences in mortality were assessed using t-tests and multiple linear regression adjusting for facility, numbers of patients utilizing the hospital and department. Results There was a significant decline in the numbers of patients seen, comparing the non-strike and strike periods; beta (ß) coefficient − 649 (95% CI -950, − 347) p < 0.0001. The physicians' strike saw a significant decline in mortality (ß) coefficient − 19.0 (95%CI -29.2, − 8.87) p < 0.0001. Nurses and Clinical Officer strikes' did not significantly impact mortality. There was no mortality increase in the post-strike period beta (ß) coefficient 7.42 (95%CI -16.7, 1.85) p = 0.12. Conclusion Declines in facility-based mortality during strike months was noted when compared to a non-striking facility, where mortality increased. The decline is possibly associated with the reduced patient volumes, and a possible change in quality of care. Public health facilities are congested and over-utilized by the local population majority of whom cannot afford even low cost private care. Health worker strikes in Kenya where the public health system is the only financially accessible option for 80% of the population pose a significant threat to universal access to care. Judicious investment in the health infrastructure and staffing may decrease congestion and improve quality of care with attendant mortality decline.